PROBLEMATIKA MEDIA ISLAM - Putri Pramesti Diana (CV. Amerta Media, 2017)
All mass media in the world, must have different ideology and interests. Throughout its history mass media have a significant influence in the development of state and cultural civilization. It agrees what McLuhan says that the media is an extension of the human mind and assumes that a major trend in any historical period is an influence of the media in power at the time. In Indonesia, the Islamic media, both print and electronic, today is quite fond of news. The case of alleged blasphemy committed by the non-active Governor of Jakarta, Basuki Tjahaja Purnama (Ahok), became a delicious meal for the Islamic media, instead of saying a common medium. Many Islamic media (not to say all of it) provide their own framing according to their ideology and interests to influence people's perceptions.Key Words: Islamic media, ideology, problematic